The Family-Owned Business Decision Making In Preserving Socioemotional Wealth - Melati Oktafiyani; Nila Tristiarini; Hayu Wikan Kinasih; Mohamed Abdulwahb Ali Alfared (Jurnal Telekomunikasi dan Informatika, 2023)
Regarding socioemotional wealth, which is derived from non-financial business elements, this study attempts to investigate the tax aggressiveness of public family-owned businesses in Indonesia. The effect of socioemotional wealth in terms of family engagement on tax aggression (measured by effective tax rate) and family generational stage as a moderator were assessed using a panel data set from 2010 to 2017 and moderated regression models using WarpPLS software version 6.0. The findings illustrate that the higher the involvement of the family in terms of ownership, management, and board of directors as well as a board of commissioners, the less tax aggressiveness. Furthermore, the findings imply that family involvement and tax behavior are not necessarily aligned and that these relationships are moderated by the family's generational stage. Considering that public family-owned business samples still exhibit the same traits as non-family-owned business, the next generation stage board of directors seems to be concerned about how aggressive tax behaviors may affect shareholder wealth and reputation.